Impact of whole-genome duplications on structural variant evolution in Cochlearia - Hämäla, Tuomas; Moore, Christopher; Cowan, Laura; Carlile, Matthew; Gopaulchan, David; Brandrud, Marie K.; Birkeland, Siri; Loose, Matthew; Kolář, Filip; Koch, Marcus; Yant, Levi (Nature Communications, 2024)
Polyploidy, the result of whole-genome duplication (WGD), is a major driver of eukaryote evolution. Yet WGDs are hugely disruptive mutations, and we still lack a clear understanding of their fitness consequences. Here, we study whether WGDs result in greater diversity of genomic structural variants (SVs) and how they influence evolutionary dynamics in a plant genus, Cochlearia (Brassicaceae). By using long-read sequencing and a graph-based pangenome, we find both negative and positive interactions between WGDs and SVs. Masking of recessive mutations due to WGDs leads to a progressive accumulation of deleterious SVs across four ploidal levels (from diploids to octoploids), likely reducing the adaptive potential of polyploid populations. However, we also discover putative benefits arising from SV accumulation, as more ploidy-specific SVs harbor signals of local adaptation in polyploids than in diploids. Together, our results suggest that SVs play diverse and contrasting roles in the evolutionary trajectories of young polyploids.
Gesehen am 05.08.2024